2000
DOI: 10.1037/1064-1297.8.4.518
|View full text |Cite
|
Sign up to set email alerts
|

How persistent is the effect of smoking urges on cognitive performance?

Abstract: Several studies have provided empirical support for S. T. Tiffany's (1990) hypothesis that drug urges interfere with cognitive performance. The authors examined the persistence of this effect. Results from an experiment involving 48 smokers and 46 nonsmokers, using a paradigm developed by R. A. Zwaan and T. P. Truitt (1998), suggest that the effect of smoking urges in cognitive performance dissipates over time. The implications of this finding for cognitive theories of drug urges and for future research on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 14 publications
5
23
1
Order By: Relevance
“…Step 1 was not significant for digit span, F(2,93) = 2.10, p>.05, or double span, found in cigarette smokers following smoking induction (Madden & Zwaan, 2001;Zwaan, Stanfield & Madden, 2000;Zwaan & Truitt, 1998), and in habitual cravers following food craving induction (Kemps et al, 2008). However, the present experiment goes further in locating the deficit in the visuo-spatial sketch pad component of working memory.…”
Section: Moderating Role Of Trait Chocolate Cravingcontrasting
confidence: 45%
“…Step 1 was not significant for digit span, F(2,93) = 2.10, p>.05, or double span, found in cigarette smokers following smoking induction (Madden & Zwaan, 2001;Zwaan, Stanfield & Madden, 2000;Zwaan & Truitt, 1998), and in habitual cravers following food craving induction (Kemps et al, 2008). However, the present experiment goes further in locating the deficit in the visuo-spatial sketch pad component of working memory.…”
Section: Moderating Role Of Trait Chocolate Cravingcontrasting
confidence: 45%
“…Because craving states are relatively transient [62,63] and delays of rewards substantially influence their relative value [60], the task was designed to be as short as possible (~90 seconds) and all alcohol and/or money selected was provided immediately following the task. To maximize the validity of the choice task, participants were provided with actual alcohol and/or money based on their choices.…”
Section: Methodsmentioning
confidence: 99%
“…Such studies have shown that smokers are slower to name the ink colour of smoking-related words than that of neutral control words in the Stroop task (Gross et al 1993;Waters and Feyerabend 2000). Similarly, presentation of smoking cues slow smokers' reaction times for targets (Sayette and Hufford 1994;Baxter and Hinson 2001), and reduce smokers' comprehension of demanding linguistic material (Zwaan and Truitt 1998;Zwaan et al 2000;Madden and Zwaan 2001) relative to control conditions. These findings demonstrate that smoking cues command limited processing resources, and thereby reduce the processing resources available for other behavioural operations.…”
Section: Introductionmentioning
confidence: 92%